PENGABDIAN KEPADA MASYARAKAT PELATIHAN PENULISAN KARYA ILMIAH BEREPUTASI BAGI GURU DI SMK NEGERI 2 BANGKALAN - Parama Diptya Widayaka; Anifah, Lilik; Tjahjaningtijas, Raden Roro Hapsari Peni Agustin; Endryansyah, Endryansyah (Universitas PGRI Adi Buana Surabaya, 2025)
Scientific work is really needed to publish work that has been made by several groups, for example lecturers in universities who always publish their research and students. However, on the other hand, teachers are also advised to write scientific articles as a condition for promotion. Not a few teachers think that writing scientific articles is very difficult so not many of them are able to publish their work in national or international journals. With this training, it is hoped that it will be able to increase teachers' motivation and competence in writing scientific papers in their future career development.